Mapping Emotions in Modern Western Europe (KULT_online, 2012)
The book Gefühlswissen: Eine lexikalische Spurensuche (Knowing the Feeling: a Lexical Search for  Traces) authored by the research group "History of Emotions" established in 2008 at the Max Planck Institute for Human Development (Berlin) under the direction of historian Ute Frevert, offers a wide variety of interdisciplinary approaches to the meanings of emotions in modernity. By providing a comprehensive analysis of German, English, and French dictionary entries of the 18th, 19th, and 20th centuries, the authors successfully show that feelings are both culturally shaped and socially learnt. Thereby emotions become conceivable as both products of historical contexts and as a history changing force. However, as a consequence of the ambivalence and vicissitude that result from the different historical, social, and political contexts in which the feelings are situated, recurrent patterns and trends are not easy to synthesize.